2023
DOI: 10.1021/acs.nanolett.3c01831
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Structural Evolution of IrFeCoNiCu High-Entropy Alloy Nanoparticles under the Acidic Oxygen Evolution Reaction

Abstract: High-entropy alloy (HEA) nanoparticles are promising catalyst candidates for the acidic oxygen evolution reaction (OER). Herein, we report the synthesis of IrFeCoNiCu-HEA nanoparticles on a carbon paper substrate via a microwaveassisted shock synthesis method. Under OER conditions in 0.1 M HClO 4 , the HEA nanoparticles exhibit excellent activity with an overpotential of ∼302 mV measured at 10 mA cm −2 and improved stability over 12 h of operation compared to the monometallic Ir counterpart. Importantly, an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 56 publications
(90 reference statements)
0
29
0
Order By: Relevance
“…In this section, we first validate the ML potential against DFT calculations for the prototypical Cantor alloy CoCrFeMnNi and comment on the suitability of 'static' approaches to evaluate segregation patterns, which are commonly used in combination with first-principles calculations [70]. Then, we perform simulations for an IrFeCoNiCu alloy and comment on the comparison with experimental data on the surface composition from [80].…”
Section: Surface Segregation In Selected Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we first validate the ML potential against DFT calculations for the prototypical Cantor alloy CoCrFeMnNi and comment on the suitability of 'static' approaches to evaluate segregation patterns, which are commonly used in combination with first-principles calculations [70]. Then, we perform simulations for an IrFeCoNiCu alloy and comment on the comparison with experimental data on the surface composition from [80].…”
Section: Surface Segregation In Selected Alloysmentioning
confidence: 99%
“…Even though obtaining a realistic description of local ordering is necessary to extract reliable estimates of thermodynamical properties, experimental conditions often require a description of kinetic effects and of the presence of a reactive environment at the surface. To investigate these effects, we consider the case of an equimolar IrFeCoNiCu HEA, for which a detailed experimental characterization of the surface composition has been recently described [80]. We first compute the Gibbs surface excess following the same protocol we used for the CoCrFeMnNi alloy.…”
Section: Irfeconicu Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…Now we turn to some current and emerging trends in the field as well as opportunities for the future. As many of the currently anticipated applications of high entropy nanoparticles are in heterogeneous catalysis, issues of bulk and surface composition as well as stability in reactive environments become increasingly important . Also important for applications in heterogeneous catalysis are a fundamental understanding and quantitative description of strain modulation throughout the particle and surface as well as of the origin and implications of synergistic effects, including electronic, magnetic, and chemical properties.…”
Section: What Is Next In the Synthesis And Characterization Of Colloi...mentioning
confidence: 99%
“…Recent studies have shown that HEA catalysts and related materials are promising for use in water-splitting electrodes, and ongoing research is focused on optimizing their properties for this application. 10–13 HEA catalysts have several advantages over the traditional catalysts used in water-splitting electrodes. First, the multiple metallic elements in the catalyst can work together to enhance the catalytic activity, resulting in a higher reaction rate.…”
Section: Introductionmentioning
confidence: 99%